Evidence for Selection in the Abundant Accessory Gene Content of a Prokaryote Pangenome. (8th May 2021) - Whelan, Fiona J; Hall, Rebecca J; McInerney, James O
Abstract: A pangenome is the complete set of genes (core and accessory) present in a phylogenetic clade. We hypothesize that a pangenome's accessory gene content is structured and maintained by selection. To test this hypothesis, we interrogated the genomes of 40 Pseudomonas species for statistically significant coincident (i.e., co-occurring/avoiding) gene patterns. We found that 86.7% of common accessory genes are involved in ≥ 1 coincident relationship. Further, genes that co-occur and/or avoid each other—but are not vertically inherited—are more likely to share functional categories, are more likely to be simultaneously transcribed, and are more likely to produce interacting proteins, than would be expected by chance. These results are not due to coincident genes being adjacent to one another on the chromosome. Together, these findings suggest that the accessory genome is structured into sets of genes that function together within a given strain. Given the similarity of the Pseudomonas pangenome with open pangenomes of other prokaryotic species, we speculate that these results are generalizable.